Documenting the Impact of Widely-Adopted CGIAR Research Innovations - Herdt, Robert W. (2018)
Innovations in agriculture generally have short-term direct effects on productivity, input use, and in-come of adopters, but they can have broader effects as well. Innovations that are widely adopted and remain in use over many years may have much wider-ranging secondary impacts, including effects on the price of the product in question and on production, and prices of substitute or complementary products. Effects may extend to urban as well as rural consumption and nutrition, and to persons living in poverty nationally. Innovations in policy-oriented research may affect such non-economic factors as the balance of decision-making between men and women.